Characterization of a novel high‐dose ovalbumin‐induced murine model of allergic sinonasal inflammation. Issue 9 (5th April 2016) - Mendiola, Michelle; Tharakan, Anuj; Chen, Mengfei; Asempa, Tomefa; Lane, Andrew P.; Ramanathan, Murugappan
Abstract : Background: Few efficacious topical therapies exist for chronic rhinosinusitis (CRS). The lack of a reproducible mouse model of CRS limits the pilot testing of potential novel anti‐inflammatory therapies. Although the ovalbumin‐induced mouse model of sinonasal inflammation is commonly used, it is difficult to reproduce and can generate variable histologic results. In this study, we explore a variation of this model in different strains of mice and explore various inflammatory cytokines as reproducible molecular markers of inflammation. Methods: Allergic sinonasal inflammation was generated in BALB/c and C57BL/6 mice using intraperitoneal high‐dose injections of ovalbumin (Ova; Sigma Chemical Co.) followed by 10 days of high‐dose intranasal sensitization. Real‐time polymerase chain reaction (RT‐PCR) for eotaxin, interleukin 4 (IL‐4), and IL‐13 were measured from sinonasal mucosa. We also pilot tested a known topical budesonide to characterize the anti‐inflammatory response. Histological sections were analyzed for epithelial thickness and eosinophilia. Results: Both BALB/c and C57BL/6 mice consistently showed increases in T helper 2 (Th2) cytokines after sensitization with high‐dose Ova ( p < 0.0001) when compared to controls. There were also significant increases in epithelial thickening in Ova‐sensitized mice and eosinophilia in both BALB/c and C57BL/6 strains. In addition, topical budesonide significantly reduced anti‐inflammatory cytokines, eosinophilia, and epithelial thickness. Conclusion: Our variation of the ovalbumin‐induced mouse model of sinonasal inflammation in both BALB/c and C57BL/6 mice provides an efficacious model for testing potential topical anti‐inflammatory therapies for CRS. The utilization of sinonasal mucosal Th2 cytokines along with histologic markers provides a consistent and quantifiable marker of inflammation in assessing the efficacy of candidate drugs.